Répétition, redondance, reformulation: les spirales explicatives du même - Ibrahim, Amr Helmy (Studia Romanica Posnaniensia, 2007)
This work tries to show how and why repetition, redundancy and rewording, by borrowing the figure of some sort of a spiral do explain and add considerably to meaning in spite o f the fact that they don’t seem to be willing to do so. Although only redundancy is likely to occur with the same shape in all languages, the three are indeed universals even if their function and place in the grammar is not the same in all languages. The paper refers to three types of ongoing different researches: that of the followers of Zellig S. Harris about redundancy seen as a complete descriptive tool of language, that of the author about repetitions in the holy Coran, and that of Claire Martinot about the way children appropriate meaning through rewordings.